PENGEMBANGAN MEDIA GAMBAR DALAM MENINGKATKAN PEMBELAJARAN MATEMATIKA - Faridah Karyati (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2017)
Learning math is one component of a series of subjects that have an important role in education that supports the development of science and technology. But until now there are many who have difficulty in doing math problems. Therefore we need the creativity and innovation of higher learning by teachers in managing learning in mathematics. One of them is to use a variety of media, including media images. This research was conducted at SDN 4 Guntung Manggis Banjarbaru. Descriptive quantitative research methods used with digging tools of observation data. Research shows that most respondents answered always 88.74% No media development drawings done by teachers in mathematics, sometimes the smallest portion 8.78% No image media development in mathematics and the smallest portion never 2,48% No picture of media development in mathematics. It is therefore recommended to teachers to always use media in learning, especially in math learning in order to improve understanding and students' motivation.Keywords: Development, media images, mathematics